New Economy, Food, and Agriculture - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (Encyclopedia of Food and Agricultural Ethics, 2019)
Consumers are becoming increasingly more informed about food systems and are interested not only in healthy, safe, and tasty food but also sustainable production, animal welfare, climate changes, and food waste. Consumers are also more focused on changing their lifestyle related to improved health knowledge and nutrition education (Timmer 2005). Maxwell and Slater (2004) have proposed criteria to evaluate food systems, including nutrition and health, rights and influence, security, sustainability, equality, and social inclusion. The authors also point out that the primary international institutions in the food value chain are not only the Food and Agriculture Organization and World Health Organization but also United Nations Industrial Development Organization, International Labour Organization, and World Trade Organization. The emerging trends in the food system are features of the new economy. This term describes the outcome of the transition from production- and manufacturing-based economy to a service-based or post-industrial economy at the end of the twentieth century. The traditional production factors such as cheap labor, land, and raw materials lose their importance in generating profits and competitiveness. The key is understanding of food consumer demand, knowledge of food industry and agriculture employees based on creativity, and flexibility of processes of production.
Keywords: O18; O34; L66; 330; Blue economy; Circular economy; Creative economy; food and agriculture; Digital economy; Sharing economy; Innovative economic systems; New economic systems